2019
DOI: 10.1093/gbe/evz250
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary basis of high-frequency hearing in the cochleae of echolocators revealed by comparative genomics

Abstract: High-frequency hearing is important for the survival of both echolocating bats and whales, but our understanding of its genetic basis is scattered and segmented. In this study, we combined RNA-Seq and comparative genomic analyses to obtain insights into the comprehensive gene expression profile of the cochlea and the adaptive evolution of hearing-related genes. A total of 144 genes were found to have been under positive selection in various species of echolocating bats and toothed whales, 34 of which were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…To date, most efforts to identify echolocation genes have examined coding sequence differences between echolocating and non-echolocating taxa, with a focus on genes implicated in audition or deafness in humans and other model organisms [17][18][19]. Results from these studies and, more recently, genome-wide screens have revealed that multiple hearing genes show molecular adaptation in lineages of echolocators, in some cases involving convergent amino acid replacements [20][21][22][23][24]. Despite insights from such comparative sequencing studies, little is known about the genetic basis of divergence in echolocation call frequencies among populations and closely related species of bats, including the role of gene expression difference (but see [25]).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most efforts to identify echolocation genes have examined coding sequence differences between echolocating and non-echolocating taxa, with a focus on genes implicated in audition or deafness in humans and other model organisms [17][18][19]. Results from these studies and, more recently, genome-wide screens have revealed that multiple hearing genes show molecular adaptation in lineages of echolocators, in some cases involving convergent amino acid replacements [20][21][22][23][24]. Despite insights from such comparative sequencing studies, little is known about the genetic basis of divergence in echolocation call frequencies among populations and closely related species of bats, including the role of gene expression difference (but see [25]).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings from Shh and SK2 and comparisons with Prestin and other genes strongly implicate multiple loci in the acquisition of echolocation in mammals ( Li et al 2010 ; Davies et al 2012 ). Recently, comparative genomic analyses have been used to unveil the genetic bases underlying adaptive evolution of echolocation in mammals ( Liu et al 2018 ; Wang et al 2020 ). A number of candidate genes responsible for echolocation and high-frequency hearing were identified; however, these warrant careful analysis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other hearing-related genes, including KCNQ4 , TMC1 , and P jvk , have also been reported to have undergone adaptive convergent or parallel evolution in echolocating mammals ( Liu et al 2011 , 2012 ; Davies et al 2012 ; Shen et al 2012 ). Furthermore, comparative genomic analyses were conducted to uncover the genetic bases for high-frequency hearing in various echolocators, and these studies have provided a large number of candidate genes involved in echolocation and ultrasonic hearing ( Thomas and Hahn 2015 ; Liu et al 2018 ; Wang et al 2020 ). Nevertheless, it is still necessary to conduct detailed and careful molecular evolutionary analyses of the candidate hearing-related genes in echolocating mammals ( Parker et al 2013 ; Zou and Zhang 2015 ; Wang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mammals show a 100-fold variation in MLS, ranging from short-lived species like forest shrews (~2 years) to long-lived species like the bowhead whale (~200 years, Tacutu et al 2018), representing an ideal lineage to study the genomics of lifespan and to unveil genes and pathways that may be relevant for humans. Numerous studies have been devoted to study mammal lifespan focusing on individual species, such as the bowhead whale (Keane et al 2015) and the naked mole rat (Kim et al 2011; Ruby, Smith, and Buffenstein 2018), or relatively small subgroups like bats (Huang et al 2019; Wang et al 2020; Seim et al 2013). While single-species studies have yielded some credible candidate genes associated with increased lifespan, it is difficult to obtain generalizations on universal mechanisms of lifespan regulation from them.…”
Section: Introductionmentioning
confidence: 99%
“…Other comparative genomics studies have focused on identifying rapid evolutionary changes in genomes or transcriptomes that correlate with changes in longevity (Kim et al 2011; MuntanĂ© et al 2018; Kowalczyk et al 2020); or have assessed the relationship between lifespan and other adaptations with life-history traits in different taxa (Montgomery and Mundy 2012; Boddy et al 2017; Wang et al 2020; Zhang et al 2014; Chikina, Robinson, and Clark 2016; Foote et al 2015). These studies have identified longevity pathways that are conserved across species, such as the insulin/IGF-1 pathway, telomere maintenance, DNA repair, coagulation and wound healing, proteostasis, and TOR signaling.…”
Section: Introductionmentioning
confidence: 99%